Hubungan Tingkat Pengetahuan dan Perilaku Mahasiswa Tentang PSN DBD Terhadap Keberadaan Jentik Aedes Aegypti di Desa Karang Asem Kecamatan Laweyan Kota Surakarta - SIAHAAN, PURNAMA PARULIAN, dr. Rochmadina Suci Bestari, M.Sc (2017)
ABSTRACT 3M mosquito nest eradication (PSN) is an easy and inexpensive method to do but in reality this does not done properly. This failure caused by the poor habits of cleanliness, the understanding and treatment of the dangers of dengue fever (DBD). This study aims to determine the relationship between the level of knowledge and behavior of students on PSN DBD to the presence of Aedes aegypti larvae in the village of Karang Asem Laweyan District of Surakarta. this study included non-experimental observational analytic with cross sectional approach, sampling taken by purposive sampling on 43 respondents. Data obtained from primary data by questionnaire and single larva examination. The statistic was analyzed by spearman test. The Results of the study were statistically with spearman test showed that there is no relationship between the level of knowledge of PSN DBD to the presence of Aedes aegypti larvae with the value of ρ = 0.464 and in behavioral level, there is a relationship between PSN DBD and the presence of Aedes aegypti mosquito larva with the value of ρ = 0.023. The conclusion from this study that there is no relationship between the level of knowledge of PSN DBD to the presence of Aedes aegypti larvae and in behavioral level, there is a relationship between PSN DBD and the presence of Aedes aegypti mosquito larva.